2007
DOI: 10.1002/cncr.22451
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and endoscopic factors predict higher pathologic grades of Barrett dysplasia

Abstract: Steady‐state and oscillatory shear behavior of three neat syndiotactic polypropylene (s‐PP) resins and a s‐PP resin (s‐PP#8) filled with CaCO3 particles of varying content, size, and type of surface modification were investigated. All of the neat s‐PP resins investigated exhibited the expected shear‐thinning behavior. Both the storage and loss moduli increased with decreasing temperature. The shift factors used to construct the master curves were fitted well with both the Arrhenius and the Williams–Landel–Ferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 51 publications
2
45
2
2
Order By: Relevance
“…21 Age, male gender, long-standing GERD, hiatal hernia size, and the length of the Barrett's esophagus are strongly associated with higher grades of dysplasia. 24,25 These preliminary results warrant further prospective evaluation as predictors of risk for the development of high-grade dysplasia (HGD) and esophageal adenocarcinoma in patients with Barrett's esophagus.…”
Section: Esophageal and Esophagogastric Junction Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Age, male gender, long-standing GERD, hiatal hernia size, and the length of the Barrett's esophagus are strongly associated with higher grades of dysplasia. 24,25 These preliminary results warrant further prospective evaluation as predictors of risk for the development of high-grade dysplasia (HGD) and esophageal adenocarcinoma in patients with Barrett's esophagus.…”
Section: Esophageal and Esophagogastric Junction Cancersmentioning
confidence: 99%
“…111 Age, male sex, longstanding GERD, hiatal hernia size, and the length of the Barrett's esophagus are strongly associated with the progression of Barrett's esophagus to adenocarcinoma of the esophagus. 24,25,112 Biomarkers such as aneuploidy and p53 loss of heterozygosity have been associated with increased risk of progression to HGD and/or adenocarcinoma of the esophagus. 112 These preliminary results warrant further prospective evaluation as predictors of risk for the development of HGD and esophageal adenocarcinoma in patients with Barrett's esophagus.…”
Section: Barrett's Esophagusmentioning
confidence: 99%
“…Up to 65-87% of BO patients have a hiatal hernia upon endoscopy. 15,[19][20][21] A case-control study comparing endoscopic findings in BO patients with HGD/OAC to patients with non-dysplastic BO found that Barrett's patients with HGD/OAC more often had a hiatal hernia (84%) than non-dysplastic patients (65%), p ¼ 0.000. Using multivariate logistic regression, the length of the hiatal hernia increased the risk of neoplastic progression with an OR of 1.2 (95% CI 1.04-1.39, p ¼ 0.013) per centimetre.…”
Section: Presence Of a Hiatal Herniamentioning
confidence: 99%
“…In a cohort study consisting of 1058 patients, the frequency and duration of heartburn symptom increase risk of BE development; presence of heartburn for more than 5 years (OR: 1.5, 95% CI 1.07-209) and the presence of daily GERD symptoms (OR: 2.33, 95% CI 1.34-4.05) were reported risk factors (19,20). The increase in the risk of detection of high-grade dysplasia is notable in long-term GERD and BE; in a cohort study consisting of 109 patients, the average was found to be 5.66 in those having complaints for more than 20 years (21). In a population-based case-control study (FINBAR) in which the relationship between GERD and BE or esophageal AC was investigated, the presence of GERD was found to be strongly associated with BE (OR: 12.0) and esophageal AC (OR: 3.48).…”
mentioning
confidence: 98%